Larval myogenesis in Echinodermata: conserved features and morphological diversity between class‐specific larval forms of Echinoidae, Asteroidea, and Holothuroidea. Issue 1 (20th January 2013) - Dyachuk, Vyacheslav; Odintsova, Nelly
SUMMARY The myogenesis of class‐specific larval forms of three classes belonging to the phylum Echinodermata (Echinoidae, Asteroidea, and Holothuroidea) was investigated via gross‐anatomy and comparative morphology of larval muscles. Using staining with phalloidin and antibodies against the muscle proteins, with subsequent CLSM and 3D imaging, we have examined myogenesis in the larvae from the gastrula stage to pre‐metamorphosis larval stages. We have shown that temporal and spatial expression of muscle proteins is similar in echinoidea and asteroidea larvae but differs in holothuroidea larvae at early developmental stages. New insights regarding the protein composition of maturing muscular fibrils during development in echinoderm larvae were detected. The first differentiating muscle structures in all tested classes have been found to be circular esophageal muscles that are associated with larval feeding. During early differentiation of echinoderm larval muscle cells, we observed that the expression patterns of the muscle proteins were not uniform but with a characteristic diffuse distribution, which is typical for smooth muscle. An unusual pattern of expression of the muscle proteins was detected in larval sphincters: the thick muscle proteins were first expressed during the early developmental stages, whereas F‐actin appeared at later stages. In addition, paired star‐shaped muscles were revealed in the mature Echinoidae plutei, but were absent in the Asteroidea, and Holothuroidea larvae. All tested species of Echinodermata exhibited both conserved features of muscle morphology during development indicating a common life history strategy and a planktonic habitat, and also an extensive morphological diversity representing specific anatomical adaptations during development.